Influential Factors of Activity Patterns and Distribution Patterns of Street Vendors in the GOR Haji Agus Salim Stadium Area on Public Space in Padang City, West Sumatra - M Yusuf Qardawi; Rinaldi Mirsa; Soraya Masthura Hassan; Effan Fahrizal; Hafizh Al Kautsar Aidilof (Electronic Journal of Education, Social Economics and Technology, 2025)
This research discusses how the activities and distribution patterns of street vendors (PKL) influence public space in the GOR Haji Agus Salim Stadium area, Padang City, West Sumatra. The increasing number of street vendors in this area has raised spatial planning issues, limited accessibility, and disrupted the original function of the stadium as a sports facility. This study uses a qualitative descriptive approach, with data collected through field observations, interviews, and documentation. The results show that PKL activities are strongly influenced by their proximity to formal sector activities and pedestrian flow. Their distribution patterns are classified into two types: clustered (focus agglomeration) and linear, following road networks (linear agglomeration). Factors influencing these patterns include strategic location, accessibility, types of goods sold, and the facilities used for vending. The study reveals that the presence of street vendors significantly affects the quality of public space visually, functionally, and in terms of comfort. Therefore, a comprehensive management strategy is needed that balances the economic needs of PKL with the order and proper use of urban space.